Spatial analysis of environmental fragility from the environmental protection area (EPA) itupararanga relief (SP) - Simonetti, Vanessa Cezar; Silva, Darllan Collins da Cunha e; Freitas, Nobel Penteado de; Rosa, André Henrique (Revista Hipótese, 2022)
Anthropogenic activities influence the quality of the environment, therefore, geotechnologies have been gaining increasing prominence in the environmental scenario. This work uses the methodology proposed by Ross (1994), for the analysis of the environmental fragility classes of the Environmental Protection Area of Itupararanga supported in a Geographic Information System environment. The results revealed that the APA has 46.85% of its classes with a high environmental fragility.
Keywords: Environmental Fragility; Geoprocessing; Declivity; Watershed